2022
DOI: 10.3390/app12105085
|View full text |Cite
|
Sign up to set email alerts
|

Histological Change in Cucumber Tissue and Cellulase Activity of Plectosphaerella melonis Strain 502

Abstract: In the last ten years, many countries around the world recorded a new disease of the Cucurbitaceae, the agent of which was P. melonis. The ability of P. melonis 502 to form intracellular mycelium in the epidermal and parenchymal tissues of roots was shown. Leading tissues (xylem and phloem) did not colonize, which indicates the impossibility of plant vessel clogging and shows the fungus’s biochemical effects on plants, which causes the process of pathogenesis. P. melonis 502 is able to develop in a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It allows the fungus to penetrate inside cells and create the intracellular mycelium. Mainly, the epiderma and parenchymatous tissues of the root are damaged, and their ruination occurs at the effect of cellulase enzymes (Patyka et al, 2022). We have also shown the growthregulating activity of P. melonis 502 and its ability to synthesize a phytohormone, ethylene .…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…It allows the fungus to penetrate inside cells and create the intracellular mycelium. Mainly, the epiderma and parenchymatous tissues of the root are damaged, and their ruination occurs at the effect of cellulase enzymes (Patyka et al, 2022). We have also shown the growthregulating activity of P. melonis 502 and its ability to synthesize a phytohormone, ethylene .…”
Section: Discussionmentioning
confidence: 61%
“…Previously we have shown that P. melonis 502 is capable of active synthesis of cellulase enzymes (exo-, endocellulases and β-glucosidases), which trigger the degradation of the cellular wall of the plant (Patyka et al, 2022). It allows the fungus to penetrate inside cells and create the intracellular mycelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations